PENGARUH JUMLAH TENAGA PENDORONG TERHADAP KECEPATAN LORI PADA PENGANGKUTAN KAYU - Apul Sianturi; Dulsalam Dulsalam (Jurnal Penelitian Hasil Hutan, 1985)
This  investigation  was carried out  in the: Padangan Forest  District,  Perum Perhutani   Unit II, East Java, employing crews of  various sizes, i.e., 4, 5 and 6 men to push the loaded  lorries.Lorry  speed  is influenced   by several factor, e.g.,  slope, crew size, team-work among  crew members. The influence  of crew size  on  lorry speed  turned  out  to  be insignificant. The average  speed of lorries  are 3.3 km/hour, 4.7 km/hour,  and 4.3 km/hour with standard error of 0.7 km/hour, 0,8 km/hour and  0,9 km/hour  for  4, 5 and  6 man, crew, respectively.